Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2021)
A dataset containing 21395549 species occurrences available in GBIF matching the query: { "and" : [ "Country is Brazil", "OccurrenceStatus is Present" ] } The dataset includes 21395549 records from 3720 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001998-210819072339941/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences